2020
DOI: 10.1021/acs.orglett.0c00870
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Annulation of Oxime Acetates with α-Amino Acid Ester Derivatives: Synthesis of 3-Sulfonamido/Imino 4-Pyrrolin-2-ones

Abstract: A copper-catalyzed annulation of oxime acetates and α-amino acid ester derivatives for the easy preparation of 4-pyrrolin-2-ones bearing a 3amino group has been developed. This process features the oxidation of amines with oxime esters as the internal oxidant to produce the active 1,3dinucleophilic and 1,2-dielectrophilic species concurrently. The subsequent nucleophilic cyclization realizes the efficient construction of 4-pyrrolin-2-one derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Exposure of N -benzenesulfonyl benzaldimine 9a to the standard condensation conditions afforded approximately 10% of the corresponding trisubstituted-2,5-dihydroimidazole 10a , suggesting a requirement for an equivalent of BF 3 ·OEt 2 . Employing an equivalent of BF 3 ·OEt 2 allowed the efficient conversion of the imine series N -benzenesulfonyl benzaldimine ( 9a ), N -phenyl benzaldimine ( 9b ), and O -acetyl cyclohexanoneoxime ( 9c ), to the corresponding dihydroimidazoles 10a – 10c (Table , entries 1–3). The anisyl group in Asmic ( 1b ) was found not to be essential as replacement with a 2-naphthyl substituent ( 1 , Ar = 2-naphthyl) allowed analogous condensations with benzaldehyde to afford 10d and with N -benzenesulfonyl benzaldimine ( 9a ) to afford 10e (Table , entries 4 and 5, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of N -benzenesulfonyl benzaldimine 9a to the standard condensation conditions afforded approximately 10% of the corresponding trisubstituted-2,5-dihydroimidazole 10a , suggesting a requirement for an equivalent of BF 3 ·OEt 2 . Employing an equivalent of BF 3 ·OEt 2 allowed the efficient conversion of the imine series N -benzenesulfonyl benzaldimine ( 9a ), N -phenyl benzaldimine ( 9b ), and O -acetyl cyclohexanoneoxime ( 9c ), to the corresponding dihydroimidazoles 10a – 10c (Table , entries 1–3). The anisyl group in Asmic ( 1b ) was found not to be essential as replacement with a 2-naphthyl substituent ( 1 , Ar = 2-naphthyl) allowed analogous condensations with benzaldehyde to afford 10d and with N -benzenesulfonyl benzaldimine ( 9a ) to afford 10e (Table , entries 4 and 5, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…[76] Some studies, however, showed that 1,3-HAT is possible in the presence of certain catalysts. [95][96][97][98][99][100][101][102][103][104][105][106] It should be noted that copper catalysis was involved in most examples where 1,3-HAT was supposed to have occurred with oxime-derived iminyl radicals.…”
Section: 3-hydrogen Atom Transfermentioning
confidence: 99%
“…In the presence of copper (I) salts oxime esters 65 underwent intermolecular cyclization with sulfonamides 66 or anilines 67 with the formation of pyrrolines 68 or 69 , respectively (Scheme 26). [101] The key stages of the proposed mechanism are shown in the bottom part of Scheme 26 on the example of substrate 67 . The authors suggested that Cu II oxidizes sulfonamides 66 and anilines 67 to the corresponding imines.…”
Section: Reactions Involving Intramolecular 1n‐hydrogen Atom Transfer To Iminyl Radical Centermentioning
confidence: 99%
“…In the past 10 years, O -acyl oximes as versatile intermediates were employed in chemical transformation for the synthesis of different heterocycles . The N–O bond in the oxime acetate is much more active than the normal N–O bond; there are many studies on the synthesis of nitrogen-containing heterocycles by breaking the N–O bond of O -acyl oximes, most of which are synthesized in the presence of transition metals, including Pd, Rh, Ru, Fe, Co, Cu, etc. In addition, microwave, UV, and visible light catalyses have also been reported.…”
Section: Introductionmentioning
confidence: 99%